Non-severe COVID-19 complicated by cytotoxic lesions of the corpus callosum (mild encephalitis/encephalopathy with a reversible splenial lesion): a case report and literature review. (December 2022) - Kubo, Mayu; Kubo, Kenji; Kobayashi, Ken-ichiro; Komiya, Nobuhiro
Abstract: Background: Coronavirus disease 2019- (COVID-19-) associated cytotoxic lesions of the corpus callosum (CLOCCs) have been reported as a rare neurological abnormality in severe cases. Here, a case of CLOCCs in the early stages of mild COVID-19 infection during the Omicron BA.1 epidemic is reported along with a literature review. Case report: A Japanese woman with COVID-19 presented to the emergency department with altered consciousness and cerebellar symptoms a day after fever onset. Magnetic resonance imaging (MRI) revealed a lesion with restricted diffusion in the corpus callosum. She exhibited no complications of pneumonia, her neurological symptoms resolved after two days, and after 10 days, the brain lesion was not detected on MRI. Literature review: The PubMed database was searched for case reports that met the CLOCC definition proposed by Starkey et al. The search yielded 15 COVID-19-associated cases reported as CLOCCs and 13 cases described under former terms, including mild encephalitis/encephalopathy with a reversible splenial lesion. Adult cases with a documented course were accompanied by pneumonia or hypoxemia, whereas pediatric cases were mostly accompanied by a multisystem inflammatory syndrome. Conclusion: COVID-19-associated CLOCCs can occur, even at an early, non-severe stage. Therefore, this condition may be underdiagnosed if MRI is not performed.